Analysis of the Prader–Willi syndrome imprinting center using droplet digital PCR and next‐generation whole‐exome sequencing. Issue 4 (21st February 2019) - Hartin, Samantha N.; Hossain, Waheeda A.; Francis, David; Godler, David E.; Barkataki, Sangjucta; Butler, Merlin G.
Abstract: Background: Detailed analysis of imprinting center (IC) defects in individuals with Prader–Willi syndrome (PWS) is not readily available beyond chromosomal microarray (MA) analysis, and such testing is important for a more accurate diagnosis and recurrence risks. This is the first feasibility study of newly developed droplet digital polymerase chain reaction (ddPCR) examining DNA copy number differences in the PWS IC region of those with IC defects. Methods: The study cohort included 17 individuals without 15q11‐q13 deletions or maternal disomy but with IC defects as determined by genotype analysis showing biparental inheritance. Seven sets of parents and two healthy, unrelated controls were also analyzed. Results: Copy number differences were distinguished by comparing the number of positive droplets detected by IC probes to those from a chromosome 15 reference probe, GABRβ3 . The ddPCR findings were compared to results from other methods including MA, and whole‐exome sequencing (WES) with 100% concordance. The study also estimated the frequency of IC microdeletions and identified gene variants by WES that may impact phenotypes including CPT2 and NTRK1 genes. Conclusion: Droplet digital polymerase chain reaction is a cost‐effective method that can be used to confirm the presence of microdeletions in PWS with impact on genetic counseling and recurrence risks for families. Abstract : Detailed analysis of imprinting center (IC) defects in individuals with Prader–Willi syndrome (PWS) is not readily available beyond high‐resolution chromosomal microarray (MA) analysis (size of defect is limited due to clinical resolution requirements) and such testing is important for a more accurate diagnosis and recurrence risk predictions. We developed three, novel droplet digital polymerase chain reaction (ddPCR) assays spanning the IC and compared our results with high‐resolution chromosomal MA and whole‐exome sequencing. Seventeen individuals with IC defects were studied along with seven sets of parents, one paternal grandmother, and two healthy, unrelated controls. We tested if the ddPCR assays could be used as a diagnostic tool and whether microdeletions in the IC, smaller than 100 kb (resolution established for commercial MA) could be identified.